2001
DOI: 10.1121/1.1345697
|View full text |Cite
|
Sign up to set email alerts
|

Functional magnetic resonance imaging measurements of sound-level encoding in the absence of background scanner noise

Abstract: Effects of sound-level on auditory cortical activation are seen in neuroimaging data. However, factors such as the cortical response to the intense ambient scanner noise and to the bandwidth of the acoustic stimuli will both confound precise quantification and interpretation of such sound-level effects. The present study used temporally "sparse" imaging to reduce effects of scanner noise. To achieve control for stimulus bandwidth, we compared 3 schemes for sound-level matching across bandwidth: component level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
54
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 53 publications
12
54
3
Order By: Relevance
“…Specifically, at cortical level, changes in sound pressure level were reflected by nonlinear (quadratic) increases of activation magnitude, with steeper slopes at the highest sound levels. While this is in agreement with some previous findings (Hart et al 2002(Hart et al , 2003, other studies reported a more or less linear increase of BOLD signal strength with sound intensity (Hall et al 2001;Langers et al 2007;Röhl and Uppenkamp 2012) and still others found indications of response saturation at the highest levels (Mohr et al 1999). To what extent these differences can be explained in terms of the use of different types of stimuli, dynamic ranges, fMRI paradigms or other factors (e.g., perceived loudness) is an interesting topic by itself, but this is not the scope of the present study.…”
Section: Response Characteristics In Relation To Sound Intensitysupporting
confidence: 94%
See 1 more Smart Citation
“…Specifically, at cortical level, changes in sound pressure level were reflected by nonlinear (quadratic) increases of activation magnitude, with steeper slopes at the highest sound levels. While this is in agreement with some previous findings (Hart et al 2002(Hart et al , 2003, other studies reported a more or less linear increase of BOLD signal strength with sound intensity (Hall et al 2001;Langers et al 2007;Röhl and Uppenkamp 2012) and still others found indications of response saturation at the highest levels (Mohr et al 1999). To what extent these differences can be explained in terms of the use of different types of stimuli, dynamic ranges, fMRI paradigms or other factors (e.g., perceived loudness) is an interesting topic by itself, but this is not the scope of the present study.…”
Section: Response Characteristics In Relation To Sound Intensitysupporting
confidence: 94%
“…While the relationship between sound intensity and neural activity in the human central auditory pathway has been extensively studied by means of neuroimaging techniques, only a small number of studies have investigated the interrelation of sound intensity, loudness and the corresponding brain activity (for a review, see Uppenkamp and Röhl 2014). Some auditory functional magnetic resonance imaging (fMRI) studies suggest that neural activation, at least in auditory cortex (AC), might be more a representation of perceived loudness rather than of physical sound pressure level (Hall et al 2001;Langers et al 2007;Röhl and Uppenkamp 2012). The current literature still does not provide definite answers to the following questions: (1) At what stage or stages along the auditory pathway is sound intensity transformed into its perceptual correlate (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…When comparing these recording types during echo processing (i.e., collapsing across Shape and Material conditions), significant activity in bilateral Heschl's gyrus as well as the occipital lobe (i.e., cuneus, MOG, fusiform gyrus) was observed, with the BOLD activity being larger for the chamber compared to the alcove recordings. Given that the alcove recordings had an overall greater mean amplitude, these results indicate that the Heschl's gyrus activation was not related to overall acoustic energy (Hall et al, 2001;Jäncke, Shah, Posse, Grosse-Ryuken, & Müller-Gärtner, 1998).…”
Section: Auditory Cortex and Echolocation In Different Acoustic Envirmentioning
confidence: 74%
“…In contrast to subcortical structures, auditory cortex has been examined in a substantial number of fMRI studies concerning sound-level dependencies (Millen et al, 1995;Jäncke et al, 1998;Mohr et al, 1999;Bilecen et al, 2002;Brechmann et al, 2002;Hall et al, 2001;Hart et al, 2002;Lasota et al, 2003;Hart et al, 2003;Mulert et al, 2005). All of these showed increases in fMRI activation magnitude and/or extent with increasing level using pure tone, complex tone, frequency modulated or speech stimuli.…”
Section: Comparison To Previous Imaging Studies Of Sound Levelmentioning
confidence: 99%
“…While tones, like noise, produce increases in fMRI activation with increasing level in auditory cortex (Hall et al, 2001;Hart et al, 2002Hart et al, , 2003, the level-dependencies of the underlying single neuron activity may be somewhat different. In contrast to the predominantly monotonic neuronal rate-level functions produced by noise in auditory cortex, there is a high proportion of non-monotonic rate-level functions for tones Phillips et al, 1994;Heil et al, 1994).…”
Section: Neural Mechanisms Behind Fmri Activation Level Dependenciesmentioning
confidence: 99%